THE ROLE OF ANTIBIOTICS DRUG PROCUREMENT PLANNING SYSTEM IN IMPROVING EFFICIENCY USING ABC CRITICAL INDEX METHOD - Mutiara, Rina; Loisa,; Kusumapradja, Rokiah; Hartati, Verani (International Journal of Psychosocial Rehabilitation, 2020)
Procurement planning of drugs in hospital pharmacy unit is important for the hospital’s health service because pharmacy unit is also included in the supporting services and main revenue center. The aim of this research is to analyze the differences value of antibiotic supplies using the ABC critical index method compared to the usual procurement planning at Hospital X. This research was observational research (non-experimental). The design of this research was descriptive evaluative using quantitative and qualitative datas that has been available. Therefore, this research can be included into a retrospective study. There were 190 kind of antibiotic drugs in 2018 and 158 kind of antibiotic drugs in 2019. This research results no significant difference between the average revenue, the usage value, the investment value, and the ABC critical index value between year of 2018 and 2019. There was difference in the average investment value based on ABC critical index method between 2018 with 2019, as in group A has the highest average investment, while group B has a moderate average investment, and group C has the lowest average investment. One of the factors that cause planning and procurement of drugs less efficient in 2018 and 2019 was the same planning and procurement system of antibiotic drugs at Hospital X every year. It is important for management team to improve the efficiency of drug planning and procurement by using ABC crital index analysis which can help management team to make decisions related to the planning and procurement of antibiotic drugs at Hospital X.